2015
DOI: 10.1186/s13005-015-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Frontal facial proportions of 12-year-old southern Chinese: a photogrammetric study

Abstract: This study aimed to establish norm values for facial proportion indices among 12-year-old southern Chinese children, to determine lower facial proportion, and to identify gender differences in facial proportions.A random population sample of 514 children was recruited. Fifteen facial landmarks were plotted with ImageJ (V1.45) on standardized photos and 22 Facial proportion index values were obtained. Gender differences were analyzed by 2-sample t-test with 95 % confidence interval. Repeated measurements were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Loveday et al also reported similar findings in photographic analysis of 200 young adult Igbos from Nigeria, with males displaying a lower third facial height than females. Olusanya et al in their research also convey similar findings [ 18 - 20 ]. On the other hand, Folaranmi et al in a study came out with an inference that no significant association exists between gender and lower facial height [ 21 ].…”
Section: Discussionsupporting
confidence: 64%
“…Loveday et al also reported similar findings in photographic analysis of 200 young adult Igbos from Nigeria, with males displaying a lower third facial height than females. Olusanya et al in their research also convey similar findings [ 18 - 20 ]. On the other hand, Folaranmi et al in a study came out with an inference that no significant association exists between gender and lower facial height [ 21 ].…”
Section: Discussionsupporting
confidence: 64%
“…It is crucial to develop population norms in order to address the averageness cue and provide information on gender differences and youthfulness (Yeung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%